Pengembangan Produk Pengolahan Pabrik Tempe Dalam Meningkatkan Pendapatan Keluarga Pada Masyarakat - Fatmawati, Ludya; Taliba, Jumalia; Yusuf, Muhamad; Zulihi, Zulihi; Fatmayanti, Anisa; Muhandy, Rachmad Surya (Ilin Institute, 2025)
The goal of this program is to process soybeans into the signature tempe of Nimbokrang, which is expected to be managed by families in the village as a home-based business. This program uses the PDCA method (planning, action, checking, and action), which includes all steps from product planning to the assistance provided. The results of this program include product analysis, packaging, marketing strategies, training in product creation, and development of entrepreneurship strategies, leading up to the launch of the tempe product. The SWOT analysis shows that the strength of this product is that it is the only one in Nimbokrang, made from high-quality soybeans. However, there is a weakness in sourcing raw materials for tempe. Limited internet access also poses a challenge in marketing through social media. On the other hand, the tempe product has good opportunities in this village and the existence of the village supports marketing. The threats include the emergence of tempe products from surrounding areas that become competitors. With attractive packaging and the right marketing techniques, it is hoped that this mentoring program can encourage families to produce tempe on a larger scale as a home industry.